2013
DOI: 10.1073/pnas.1300963110
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobases bind to and stabilize aggregates of a prebiotic amphiphile, providing a viable mechanism for the emergence of protocells

Abstract: Primordial cells presumably combined RNAs, which functioned as catalysts and carriers of genetic information, with an encapsulating membrane of aggregated amphiphilic molecules. Major questions regarding this hypothesis include how the four bases and the sugar in RNA were selected from a mixture of prebiotic compounds and colocalized with such membranes, and how the membranes were stabilized against flocculation in salt water. To address these questions, we explored the possibility that aggregates of decanoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 23 publications
(23 reference statements)
7
119
0
1
Order By: Relevance
“…Venter and coworkers' Mycoplasma laboratorium experiment (92) or Michael Crichton's Jurassic Park fiction both require placing remodeled or renewed DNAs into a preexisting cell. To completely create life in vitro, synthetic RNAs need to be wrapped inside a man-made bilayer vesicle, as being attempted in the Szostak laboratory (93,94) and elsewhere (95). Mother Nature took her time with available material.…”
Section: The Originmentioning
confidence: 99%
“…Venter and coworkers' Mycoplasma laboratorium experiment (92) or Michael Crichton's Jurassic Park fiction both require placing remodeled or renewed DNAs into a preexisting cell. To completely create life in vitro, synthetic RNAs need to be wrapped inside a man-made bilayer vesicle, as being attempted in the Szostak laboratory (93,94) and elsewhere (95). Mother Nature took her time with available material.…”
Section: The Originmentioning
confidence: 99%
“…Recently, it was shown that a possible prebiotic amphiphile (decanoic acid) undergoes distinct binding interactions with nucleobases and proteins [30,31]. So, at this stage, they may serve as containments for initial metabolic steps and, most prominently, as an ensemble of encapsulated environments for the replication of RNA molecules.…”
Section: Possible Mechanisms Of Vesicle-induced Molecular Evolutionmentioning
confidence: 99%
“…As for the other heterogeneous media, the lipid matrices could also have played some significant, additional roles in the emergence of compartmentalized precellular systems or protocells (the nucleic acid products can be encapsulated in the reforming vesicles during rehydration) [75,113] or even in the selection of nucleobases from the “prebiotic soup” [114]. …”
Section: Heterogeneous Media As Supporting Environments For Rna Pomentioning
confidence: 99%